Predictive models for the assessment of occupational exposure to chemicals: A new challenge for employers - Jan Piotr Gromiec; Małgorzata Kupczewska-Dobecka; Agnieszka Jankowska; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2013)
Employers are obliged to carry out and document the risk associated with the use of chemical substances. The best but the most expensive method is to measure workplace concentrations of chemicals. At present no "measureless" method for risk assessment is available in Poland, but predictive models for such assessments have been developed in some countries. The purpose of this work is to review and evaluate the applicability of selected predictive methods for assessing occupational inhalation exposure and related risk to check the compliance with Occupational Exposure Limits (OELs), as well as the compliance with REACH obligations. Based on the literature data HSE COSHH Essentials, EASE, ECETOC TRA, Stoffenmanager, and EMKG-Expo-Tool were evaluated. The data on validation of predictive models were also examined. It seems that predictive models may be used as a useful method for Tier 1 assessment of occupational exposure by inhalation. Since the levels of exposure are frequently overestimated, they should be considered as "rational worst cases" for selection of proper control measures. Bearing in mind that the number of available exposure scenarios and PROC categories is limited, further validation by field surveys is highly recommended. Predictive models may serve as a good tool for preliminary risk assessment and selection of the most appropriate risk control measures in Polish small and medium size enterprises (SMEs) providing that they are available in the Polish language. This also requires an extensive training of their future users. Med Pr 2013;64(5):699-716